El procedimiento de aplicación de la reinversion del impuesto a la renta y su incidencia en los institutos privados de educacion superior del distrito de Trujillo 2006 - 2008 - Alvarado Cáceres, Elena Jesús (2010)
To investigate the procedure for applying the proceeds from the reinvestment of income earned by five institutes of Higher Education Technical Private Trujillo District during the period 2006 to 2008 in order to demonstrate the proper use of such tax benefit, and thus knowing its impact on the quality of education. We have used direct and indirect sources of information as well as formats for the collection, storage and retrieval of information to assess reinvestment plans and implementation of income generated by the Institutes. This information was contrasted with the results from the application of SERVQUAL model, which defines service quality as the difference between perceptions by customers of the service and all expectations. Thus, a negative or positive customer quality of service when perceptions that it has obtained are below or above the expectations I had. In order to get such information, a survey to 331 students of institutes of the city of Trujillo, determining that there is need for proper planning before developing and sending Sunat reinvestment plans and the Ministry of Education, that the order to achieve a positive effect on the quality of education provided to students, since otherwise the benefit will not be an adequate response to the problems that arise in educational institutions as a result of lack of resources and infrastructure, teacher training, technology and equipment suitable for level of education. The paradox is that the Legislative Decree No. 882 Education Reinvestment Act was created with the purpose of educational institutions in general to reinvest their income in order to improve the quality and efficiency of service. It has been noted that educational institutions have been profitable, but the interest of reinvestment of income not being properly implemented to achieve satisfaction in the service, not making a positive impact on the student.